Giant compound odontoma of the mandible in an adolescent - Van Trung Hoang; Hoang Anh Thi Van; Thanh Tam Thi Nguyen; Di Thu Hoang Le; Nhu Quynh Vo; Tien Hoai Vo; Vichit Chansomphou; Ngoc Trinh Thi Pham; Cong Thao Trinh; Riccardo Aiuto (Elsevier, 2021)
Odontomas are one type of benign odontogenic hamartoma that includes the compound and complex odontoma. They are generally reported not to exceed 3 cm in diameter. Odontomas with a diameter exceeding 3 cm are considered giant odontomas. An accurate diagnosis of odontomas cannot be made during the clinical examination. The majority of compound odontoma is diagnosed most commonly during radiographic screening. It should be done in coordination with a histological examination after surgical treatment. We report a case of giant compound odontoma of the mandible in a young boy. The tumor is treated by surgical excision under general anesthesia.